1991
DOI: 10.1017/s0021932000019234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of socioeconomic factors on secular trends in suicide in Japan, 1953–86

Abstract: The effects of socioeconomic factors on secular trends in suicide rates in Japan for the periods 1953-72 and 1973-86 were investigated using twelve socioeconomic indicators. Multiple regression analysis showed that the socioeconomic indicators affecting suicide rates were not identical in the two periods. The rates in both sexes in 1953-72 were closely related to unemployment rate and the labour force but between 1973 and 1986, divorce rate and the proportion in tertiary industry were most influential. The cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Motohashi's study revealed that unemployment rate related closely to suicide mortality in both genders during 1953-72, while divorce rate and proportion in tertiary industry influenced on suicide during 1973-86 (Motohashi, 1991). The transition of industrial structure in Japan from an industrial to a service economic one could explain this kind of difference (Motohashi, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motohashi's study revealed that unemployment rate related closely to suicide mortality in both genders during 1953-72, while divorce rate and proportion in tertiary industry influenced on suicide during 1973-86 (Motohashi, 1991). The transition of industrial structure in Japan from an industrial to a service economic one could explain this kind of difference (Motohashi, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The transition of industrial structure in Japan from an industrial to a service economic one could explain this kind of difference (Motohashi, 1991). However, during the late 1990s and early 2000s when the Asian financial crisis broke out, unemployment and personal bankrupt rate were positively associated with Japanese male suicide (Watanabe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…While the national unemployment rate exceeded 4.0 percent in 1998-2000, the rate had been below 2.0 percent in 1970-1975.7 Motohashi reported that the changes in socioeconomic structure influenced the epidemiological characteristics of suicide rates. 15 We suspect that the effects of savings on suicide might vary, depending on the economic background.…”
Section: Discussionmentioning
confidence: 99%
“…The nine social life indicators were selected as they were available every year for a long period after the Second World War, and they were assumed to affect suicide mortality directly or to be possible confounding factors by careful examination of previous literatures 1, [4][5][6][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Methodsmentioning
confidence: 99%